Produtividade total dos fatores e capacidade de absorç\~ao tecnológica na agropecuária paulista - José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Technological change is a determining factor in economic growth. Since the 1970s, Brazil has become an example in promoting agricultural research. The result was total factor productivity (TFP) growth. What would be the impact of public policies on productivity growth? The present study sought to break down some factors that influenced TFP, particularly in the state of S\~ao Paulo. Overall, the main findings showed that training, research, extension, and promotion, together, caused TFP. In the impulse-response function, there was a positive impact on productivity in the main science and technology (S&T) variables. It should be concluded that spending on S&T was important to increase productivity.
Keywords: C01; O3; O4; 330; productivity; science and technology; growth; agriculture